High-Strength Iron Wire-Like Carbon Nanotubes in the Construction of a Digital Smart Logistics Supply Chain System - Jie He; Wenqing Miao (Advances in Materials Science and Engineering)
Today, modern logistics and transportation as a whole still have many problems such as high cost, low efficiency, and poor service quality. This article aims to improve the efficiency of various logistics departments. In order to explore the role of high-strength steel wires as carbon nanotubes in the construction of digital logistics systems, this article saves manpower and management costs in the logistics process and effectively manages information transportation and operating costs by sensing and controlling automated processing and operating procedures. It can effectively solve technical problems and create a complete logistics system that meets product needs. The results of the study show that through the transformation of traditional logistics through carbon nanotubes, the efficiency of digital logistics is relatively stable, with an average value of about 2.5, which takes more than 30% less time than traditional logistics.